The clinical relevance of serum CYFRA 21-1 assay in patients with ovarian cancer. Issue 4 (1st June 2001) - Gadducci, A.; Ferdeghini, M.; Cosio, S.; Fanucchi, A.; Cristofani, R.; Genazzani, A. R.
Abstract : Abstract: Gadducci A, Ferdeghini M, Cosio S, Fanucchi A, Cristofani R, Genazzani AR. The clinical relevance of serum CYFRA 21-1 assay in patients with ovarian cancer. CYFRA 21-1 assay, which detects serum fragments of cytokeratin 19, has been widely assessed as a serum marker of several malignancies. Preoperative serum CYFRA 21-1 levels were retrospectively measured in 60 patients with ovarian cancer and in 59 control patients with benign ovarian disease. CYFRA 21-1 levels were also serially measured in 90 serum samples drawn from patients with advanced (FIGO stage III-IV) ovarian cancer followed after surgery and chemotherapy. Preoperative serum CYFRA 21-1 levels were higher in patients with ovarian cancer compared with controls (median, range = 2.6, 0.1–51.4 ng/ml versus 0.4, 0.0–3.6 ng/ml, P < 0.0001), and among the former, antigen values were higher in the 39 patients with advanced-stage than in the 21 patients with early (FIGO stage I-II) disease ( P < 0.0001). In advanced ovarian cancer patients, the 25%, 50%, and 75% quantiles of preoperative CYFRA 21-1 levels were 1.9, 4.8 and 14.4 ng/ml, respectively. Preoperative CYFRA 21-1 levels were lower in the 11 patients who achieved a pathologic complete response at second-look compared with those who had clinically or surgically detectable persistent disease after first-line chemotherapy (median, range 1.9, 0.6–9.2 ng/ml versus 10.2, 0.1–51.4 ng/ml, P = 0.007). The pathologic complete response rate was significantly greater in patients with low preoperative CYFRA 21-1 levels compared with those with elevated CYFRA 21-1 levels at any cut-off limit for the antigen (1.9, 4.8 and 14.4 ng/ml). However, Cox regression analysis failed to detect a significant association between preoperative CYFRA 21-1 assay and survival. As for the follow-up of advanced ovarian cancer patients, CYFRA 21-1 levels were higher in the 42 samples drawn from patients with clinically detectable disease compared with the 48 specimens collected from patients with no clinical evidence of disease (median, range = 1.15, 0.3–40.7 ng/ml versus 0.4, 0.1–9.1 ng/ml, P < 0.0001). In conclusion, preoperative serum CYFRA 21-1 assay appears to be predictive of response to chemotherapy, but not prognostic of survival, for patients with advanced ovarian cancer. Moreover, the serial measurement of CYFRA 21-1 levels might have a potential clinical relevance for the assessment of disease status in patients followed after surgery and chemotherapy.